Strategic partnership with AMIK Tunas Bangsa and STIKOM Tunas Bangsa - Nor Salwana, Mohammad Idris (2017)
Universiti Malaysia Pahang (UMP) has signed memorandum of understanding with Akademik Manajemen Informatika dan Komputer (AMIK) Tunas Bangsa focusing in academic and student exchange program that will be beneficial to both parties. This networking also involves Tunas Bangsa High Technology Computer School, (STIKOM), Indonesia.